Enterprise supply chain management : integrating best-in-class processes - Sehgal, Vivek (Hoboken, N.J. : Wiley, 2009)
This book presents a functional approach of looking at the enterprise supply chain including technology, financial, and operational issues. This book provides an enterprise view of the supply chain functions and describes the underlying concepts for these processes, what they achieve, and how they are executed. It covers the planning and execution processes for demand, supply, and logistics management and explains how supply chains are modeled for optimal performance. Written in a clear, concise, and easy-to-understand fashion, drawing examples from diverse industry verticals, this book is equally useful to the business and the IT managers. Vivek Sehgal (Atlanta, GA) is Director of Research at Manhattan Associates, a global, best-of-breed supply chain solutions provider, with over 1,200 customers worldwide. -- Publisher description.
What is a supply chain? -- Scope of the supply chain -- Supply chain planning -- Supply chain network design -- Demand planning -- Supply planning -- Supply chain execution -- Supply Management -- Transportation management -- Warehouse management -- Reverse logistics manaagement -- Supply Chain Collaboration -- Collaborative processes -- Supply chain technology -- RFID technology -- Understanding cross-docking -- Supply chain and finance: a quick primer -- How green is your supply chain? -- Commonly used EDI -- Incoterms (International commercial terms).
Includes index.
Print version record.
John Wiley and Sons
Keywords: Business logistics; Logistique (Organisation); BUSINESS & ECONOMICS -- Industries -- General; TECHNOLOGY & ENGINEERING -- Industrial Technology; TECHNOLOGY & ENGINEERING -- Industrial Engineering; BUSINESS & ECONOMICS -- Production & Operations Management; Business logistics; Supply Chain Management; Ketenbeheer (logistiek)